Syntheis of new chiral 5,6,7,8-tetrahydrotetrazolo[1,5-a]pyrazines from alpha-amino acid derivatives following ``click'' chemistry - Mohapatra, Debendra K.; Maity, Pradip K.; Ghorpade, Ravindra V.; Gurjar, Mukund K. (Heterocycles, 2009)
An efficient and practical synthesis of new chiral fused tetrazoles have been synthesized following [3+2] cycloaddition reaction starting from alpha-amino acid derivatives.
Keywords: Amino acid; Click chemistry; Hypertension; Nitrogen Rich System; Tetrazole

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Non-isothermal kinetics of free-redical polymerization of 2-phenyl ethyl acrylate, paper presented at ?third international multicomponent polymer conference? impc 2012 - Ghorpade, Ravindra V.; Rajdeo, K. S.; Ponrathnam S.; Chavan N. N. (Third International Multicomponent Polymer Conference IMPC 2012, Kottayam, India., 2012)

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.

PolyHIPE derived freestanding 3D carbon foam for cobalt hydroxide nanorods based highperformance supercapacitor - Patil, Umakant M.; Ghorpade, Ravindra V.; Nam, Min Sik; Nalawade, Archana C.; Lee, Sangrae; Han, Haksoo; Jun, Seong Chan (Scientific Reports, 2016)
The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)(2)) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)(2)/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 degrees C to obtain graphitic 3D carbon foam with high surface area (389 m(2) g(-1)) having open voids (14 mu m) interconnected by windows (4 mu m) in monolithic form. Moreover, entangled Co(OH)(2) NRs are anchored on 3D GCF electrodes by using a facile chemical bath deposition (CBD) method. The wide porous structure with high specific surface area (520 m(2) g(-1)) access offered by the interconnected 3D GCF along with Co(OH)(2) NRs morphology, displays ultrahigh specific capacitance, specific energy and power. The Co(OH)(2)/3D GCF electrode exhibits maximum specific capacitance about similar to 1235 F g(-1) at similar to 1 Ag-1 charge-discharge current density, in 1 M aqueous KOH solution. These results endorse potential applicability of Co(OH)(2)/3D GCF electrode in supercapacitors and signifies that, the porous GCF is a proficient 3D freestanding framework for loading pseudocapacitive nanostructured materials.

Prediction of reactivity ratios in free radical copolymerization from monomer resonance-polarity (Q-e) parameters: genetic programming-based models - Shrinivas, K.; Kulkarni, Rahul P.; Shaikh, Saif; Ghorpade, Ravindra V.; Vyas, Renu; Tambe, Sanjeev S.; Ponrathnam, S.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2016)
The principal deficiency of the widely utilized Alfrey-Price (AP) scheme for computing reactivity ratios in the widely used free radical copolymerization is that it ignores important factors, such as the steric effects. This often leads to inaccurate reactivity ratio predictions by AP model. Accordingly, in this study, exclusively data-driven, Q-e parameter-based new models have been developed for the reactivity ratio prediction in free radical copolymerization. In the model development, a novel artificial intelligence formalism known as ``genetic programming (GP)'' that performs symbolic regression has been employed. The GP-based models possess a different functional form than AP model. Further, parameters of GP-based models were fine-tuned using Levenberg-Marquardt (LM) nonlinear regression method. A comparison of AP, GP and GP-LM as well as artificial neural network (ANN)-based models indicates that GP and GP-LM models exhibit superior reactivity ratio prediction accuracy and generalization performance (with correlation coefficient magnitudes close to or greater than 0.9) when compared with AP and ANN models. The GPbased reactivity ratio prediction models developed here due to their higher accuracy and generalization capability have the potential of replacing the widely used AP models.
Keywords: Alfrey-Price scheme; free radical copolymerization; genetic programming; reactivity ratio; symbolic regression

Synthesis and characterization of thermally stable polyimides with a pendent phenothiazine unit based on new diamine 10-(3,5-diaminobenzoyl)phenothiazine - Ghorpade, Ravindra V.; Thorave, Asmita K.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (High Performance Polymers, 2016)
A novel diamine 10-(3,5-diaminobenzoyl)phenothiazine (DBPT) with a side chain containing phenothiazine unit was synthesized. A new family of polyimides (PIs) containing phenothiazine unit in the side chains has been successfully synthesized by direct polycondensation of DBPT with pyromellitic dianhydride, 3,3',4,4'-benzophenone tertacarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride (ODA) via a conventional two-step chemical imidization process. The yield of polymers was good enough, which were soluble in most organic solvents. The molecular orbital energy gaps, thermal stability, and crystallinity of PIs were investigated by molecular modeling, thermogravimetric analysis, and wide-angle X-ray scattering, respectively. Thermal properties of polymers were good enough to permit the use of these PIs in various applications; only 49% weight loss is detected at 900 degrees C in nitrogen atmosphere. X-Ray diffraction clearly reveals the amorphous nature of PIs. A quantum modeling study (density functional theory) has shown the influence of dianhydride structure on the energy difference of highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels.
Keywords: phenothiazine-containing diamine; Polyimide; thermally stable polymer

Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties

Epoxy functionalized polymer grafted magnetic nanoparticles by facile surface initiated polymerization for immobilization studies of Candida Antarctica lipase B - Afzal, Haq Asif; Ghorpade, Ravindra V.; Thorve, Asmita K.; Nagaraja, Sreeharsha; Al-Dhubiab, Bandar E.; Meravanige, Girish; Rasool, Sahibzada Tasleem; Roopashree, Teeka S. (Reactive & Functional Polymers, 2020)
Immobilization of Candida Antarctica lipase B (Cal-B) was done on the epoxy functionalized polymer (EFP) grafted magnetic nanoparticles (MNPs) via covalent attachment with the active epoxy groups. The EFP brushes were grafted on iron-oxide based MNPs by a facile surface-initiated atom transfer radical polymerization (ATRP) using activators generated by electron transfer (AGET) of glycidyl methacrylate (GMA). Each step of the surface modification, polymer grafting, and enzyme immobilization process on the polymer grafted MNPs was studied using Fourier transform infrared spectroscopy (FTIR). A thermogravimetric analysis (TGA) calculated the amount of engineered organic components, a transmission electron microscopy (TEM) visualized the core-shell formation of the MNPs, and a vibrating sample magnetometer (VSM) validated their magnetic properties at various modification stages. The lipase immobilization efficiency was described as a function of immobilization time, as well as, enzyme amount. The activity was characterized within a range of pH, temperature, kinetic parameters, resusability and storage stability, for both the free and immoblized Cal-B enzyme. The results of this study suggested that poly(GMA) grafted MNPs can be successfully used for the immobilization of Cal-B with improved efficiencies compared to those obtained with free soluble lipase. The reported enzyme immobilization method appears to be reproducible and scalable for industrial production.
Keywords: Cal-B enzymes; enzymes; Immoblization; Magnetic nanoparticles